2022
DOI: 10.47372/ejua-ba.2022.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Cytomegalovirus Among Pregnant Women in Ad-Dhale'e City - Yemen

Abstract: This study aimed to determine the seroprevalence of Cytomegalovirus virus (CMV) infection among pregnant women in Ad Dhale'e city, Yemen. A cross-sectional study was conducted among 130 pregnant women attended for routine antenatal care in Al-Nasser hospital in Ad-Dhale'e city. Serum was obtained and tested for seropositivity of CMV IgG and IgM using electro-chemiluminescence immunoassays  (ECLIA) test. Of 130 blood sample, 122 (93.8 %) and 5 (3.8%) were identified with CMV IgG and CMV IgM seropositive respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a similar study, the high rate of HCMV infection was among pregnant women in the age group of 15-25 years [10] and 14-30 years [13]. This study is inconsistent because it documented that the high rate of HCMV infection was among pregnant women in the age group of 25-34 years (97.3%) [14] and 31-40 years [12]. In general, the frequency of HCMV is higher among women, people in older age brackets, people with lower socioeconomic status, and people in developing countries.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a similar study, the high rate of HCMV infection was among pregnant women in the age group of 15-25 years [10] and 14-30 years [13]. This study is inconsistent because it documented that the high rate of HCMV infection was among pregnant women in the age group of 25-34 years (97.3%) [14] and 31-40 years [12]. In general, the frequency of HCMV is higher among women, people in older age brackets, people with lower socioeconomic status, and people in developing countries.…”
Section: Discussionmentioning
confidence: 96%
“…According to the current results, those who studied in secondary schools (46.2%) had the highest rate of HCMV prevalence. Different studies found a high proportion of HCMV infections in pregnant women with basic levels of education [10,14]. In terms of gestational stage, pregnant women experienced the highest rate of HCMV infection in their second trimester (65.4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV belongs to the subfamily Betaherpesvirinae and is recognized as the most common congenital viral infection in humans, with an estimated global seroprevalence of 83% (95% uncertainty interval [UI], 78 to 88) ( 4 ). There are, however, regions with reported CMV seroprevalences in adults of up to 100% ( 5 ). EBV, which infects 90 to 95% of humans worldwide, is a gammaherpesvirus and is the causative agent of infectious mononucleosis ( 6 ).…”
Section: Introductionmentioning
confidence: 99%